(untitled) - Hirschmeier, J. (Boston, 1975)
This book has bên writen as an aoutline history of the development of Japanese business. A good deal of literaturre exists on some aspects, and some periods.
Keywords: Industrial management,Japan,Quản trị công nghiệp,Nhật Bản; Commerce,Thương mại; Japan,Nhật Bản